Determinant Factors of Green Marketing Adoption in the Hospitality Sector - Liviu B. Vlad; Dragoş C. Vasile; Octav-Ionuţ Macovei; Claudia E. Ţuclea (Amfiteatru Economic)
Green marketing is falling into the category of answers provided by the business world to the requirement to combine the economic development with the preservation of natural resources which represents a pressing concern of the modern times. In this context, the hospitality sector is facing as well an increasing pressure to pay attention to environmental issues, hotel organizations are increasingly tending to use environmentally friendly products and services, and to implement programs to manage energy and water consumption and waste. The adoption of green marketing in hospitality industry is significantly facilitated by internal and external factors. The paper focuses on the analysis of determinant internal factors: first and foremost on the pro-environmental behavior of the hotel managers and employees, and also on the already implemented green practices in the daily hotel activity. The implementation of green marketing strategies further examined being taken into account the organizational change theory, discloses a third determinant factor, namely, to what extent the process of changing is prepared. This paper is advancing an integrated model of determinant internal factors of green marketing implementation in the hospitality sector. The proposed research model has been tested and validated after analyzing the data collected in a quantitative research conducted on 330 managers and employees from the hospitality industry in Romania. The results show that the three predictors - pro-environmental behavior, current green practices and the change readiness - are having a significant influence on the implementation of green marketing.